Daily sources of radiation in our environment: Potential Exposure beyond hospitals - Yus, Teuku M.; Wijaya, Anandhika; Satria, Darma; Riany, Khairida; Abdullah, Masna D. (Trends in Infection and Global Health, 2024)
Radiology examinations play a vital role in healthcare worldwide, but patient safety, particularly radiation protection, remains a key concern for all stakeholders. Despite this, some patients and their families still express concerns about the impact of radiation from radiology exams. Healthcare workers, including radiographers, radiologists, interventional surgeons, interventional cardiologists, and others, often find themselves explaining these concerns repeatedly before procedures. Misconceptions about the effects of radiation from medical examinations may stem from misinformation encountered by patients in the past. In reality, people are exposed to various environmental radiation sources daily, often without being aware of it, although the doses are typically low. The goal of this study was to explore the radiation sources that individuals are potentially exposed to on a daily basis. By integrating the ALARA (As Low As Reasonably Achievable) principle into radiological practice, the public should feel more reassured and less anxious about the risks. Thus, it is important for people to understand the sources of radiation in their everyday environment.